STUDENTS’ LEARNING OUTCOMES IN A DIFFERENTIATED INSTRUCTIONAL APPROACH IN GRADE 8 SCIENCE (Proceedings of the International Conference on Social Sciences, 2023)
The study investigated the students’ learning outcomes through differentiated instructional approach in grade 8 science in Valencia National High School, Valencia City, Bukidnon.  Specifically, the study aimed to: determine the level of students’ academic performance; ascertain the attitudes of students; find out the  significant difference between students’ academic performance; and find out the  significant difference between students’ attitudes as exposed to non-differentiated instructional approach  and differentiated instructional approach.  Quasi-experimental research design was used to determine the students’ learning outcomes in the two sections of Grade 8 science.  The instruments made use of academic and non-academic assessment.  Analysis of Covariance (ANCOVA) was used to determine any significant difference on students’ academic performance.The use of differentiated instructions namely: content, process and product had exhibited an increase on students’ academic performance in science.  These results had provided a gratifying experience among students such that they performed better and gained high scores on their tests.  With differentiated instruction, the students fostered positive attitude toward the importance of science, the learning of science outside of school, the learning of science in school, practical work in science, future participation in science and self-concept in science as indicators on which students showed more intensively and demonstrated favorable attitudes toward the subject.  The students’ academic performance between two groups indicated high significant difference; thus, students’ engagements for learning through differentiated instruction were found to perform better than in non-differentiated instruction.   Analysis on students’ attitudes toward science showed no significant difference between groups.
Keywords: academic performance, content,differentiated instruction, process, product and student’s attitude.